Obraz Grecji w mowie wyzwolenczej Georgiosa Papandreu z 18 pazdziernika 1944 r. - Gortych, Karolina (Investigationes Linguisticae, 2005)
In the first part of the article some remarks about rhetoric in politics are presented. The second part is the first Polish translation of Georgios Papandreou’s speech of 18 February 1944. The third part includes a commentary with reference to rhetorical methods of argumentation used in the translated speech.